EVOLUTION OF AUTONOMOUS MOBILE FIRE EXTINGUISHING EQUIPMENT - Abramov, Y.; Sobyna, V.; Soshinskiy, О. (Municipal economy of cities. Series: «Economy science», 2023)
It is shown that the evolution of autonomous mobile fire-extinguishing means includes four stages, in which these fire-extinguishing means are divided into portable, wearable, mobile and mobile. All these fire extinguishing means are united by the presence of a human operator. Portable fire extinguishing equipment is characterized by a small weight, which does not exceed 20 kilograms. Portable fire extinguishing equipment has a greater mass (up to 30 kilograms) and, as a result, a longer duration of extinguishing agent supply (up to 75 seconds). Such tools have improved ergonomic characteristics, and the possibility of using gel-forming substances as fire-extinguishing substances gives them new properties. It is noted that such fire-extinguishing substances provide record values of the coefficient of use. Mobile fire extinguishing equipment provides a longer duration of extinguishing agent supply and relieves the operator. All these fire extinguishing means are united by the fact that their operational capabilities are limited by the low speed of their movement, the value of which does not exceed 1.2 meters per second. The fourth stage of the evolution of autonomous mobile firefighting equipment is characterized by the placement of firefighting equipment on a mobile base. A segway can act as such a base, as a result of which the operational capabilities of the fire extinguishing agent are significantly expanded. It is noted that the speed of movement of such fire extinguishing means can reach 50 kilometers per hour with a radius of action of up to 50 kilometers. The mass of the fire-extinguishing substance in such fire-extinguishing means can reach (40-50) kilograms, and the duration of its supply is up to 40 seconds. It is shown that in mobile fire-extinguishing equipment, the task of matching the characteristics of the operator with the technical characteristics of the fire-extinguishing equipment is relevant. This is especially important for mobile fire extinguishing equipment. Examples of determining the parameters of the human operator and their use in mobile fire extinguishing equipment are given.